Peran mediasi self-efficacy pada work engagement dan perceived organizational support - Devina Andriany; IJK Sito Meiyanto (Fakultas Psikologi, 2021)
Excellent human resources in the organization are seen as the principal capital for the company to improve the company’s role, function, and competitiveness in facing developments and changes both internally and externally. Companies with high-stress levels need superior employees that motivated, passionate about work and loyal to the organization. These needs can refer to the characteristics of employees who are engaged with their work. However, there are still many dynamics of psychological constructs that have not been revealed that can increase work engagement. The purpose of this study was to determine whether self-efficacy can be a mediator on the effect of perceived organizational support (POS) on work engagement. The research was conducted through a survey method taken from 103 bank marketing employees. The collected data were analyzed through the structural equation model (SEM) and showed an indirect effect of perceived organizational support on work engagement (ab = 0.13; p≤0.001). This result shows that self-efficacy partially mediates the relationship between perceived organizational support (POS) and work engagement and the research hypothesis is acceptable. Keywords: SEM, work engagement, perceived organizational support, self-efficacy